Local Efficacy of Corticosteroids as an Adjuvant for Periarticular Cocktail Injection in Simultaneous Bilateral Total Knee Arthroplasty: A Prospective Randomized Double-Blind Controlled Trial - Huiming Peng; Wei Wang; Jin Lin; Xisheng Weng; Wenwei Qian; Wenda Wang (Pain Research and Management)
Multimodal cocktail periarticular injections comprising corticosteroids are the most suggested therapy for postoperative discomfort and swelling following total knee arthroplasty (TKA). Nevertheless, previous findings cannot be applied to instances of unilateral total knee arthroplasty on bilateral knees. This randomized, prospective, double-blind, controlled clinical study examines the efficacy as well as safety of periarticular multimodal cocktail injection along or sans corticosteroids in certain situations. The 60 patients (120 knees) that experienced concurrent bilateral total knee arthroplasty were provided periarticular injections along additional betamethasone (7 mg) in the randomized knee, as well as the other knee, where corticosteroid was not administered. Key results were “pain scores at rest as well as in action” on a visual analogue scale of 11 pt. Other results included motion range, swelling of the thigh, Hospital for Special Surgery score (HSS score), and adverse effects were measured between the two sides. No statistically promising variations were found in the visual analogue scale ranking, motion range, girth of the thigh, and HSS score, as well as complications between the two sides. The impact on treatment outcomes was maintained between the knees on postoperative day 3 or at 3 months of follow-up. Multimodal periarticular injection without corticosteroid will alleviate postoperative swelling and pain. More studies are needed for the use of betamethasone as a corticosteroid in periarticular multimodal cocktail injections. This Chinese Clinical Trial Registry is registered with ChiCTR-OPC-17013503, dated 2017-11-23, available from http://www.chictr.org.cn/showproj.aspxproj=23146.